Paham Inkar Sunah di Sumatera Utara: Studi Tentang Argumentasi dan Perkembangannya - Nawir Yuslem; Sulidar Sulidar; Suhaidi Arfan; T. Wildan (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
The Inkar Sunnah Order in North Sumatra: A Study of Argumentation and Its DevelopmentThis study aims to determine the development and arguments of the Inkar Sunah understanding, especially in North Sumatra; Inkar Sunah understanding; even though there has been a ban from the Indonesian Council of Ulama (MUI: Majelis Ulama Indonesia), its existence still exists and is active in people's lives. This research is qualitative using a library research approach; the descriptive analysis method is used to describe and analyze research data, data collection by observation, interviews and documentation to the Indonesian Council of Ulama (MUI); after the data collected will be reduced, presented and draw a conclusion. Research findings include; that in the development of the Inkar Sunah in North Sumatra, there is an understanding that rejects the hadith/sunnah and indirectly rejects the Qur’an due to not understanding the method of interpreting the Qur’an by the standards that the commentator has prepared. Thus, a group of Inkar Sunah reject the sunnah of the Prophet saw and leave the Qur’an. Inkar Sunah in North Sumatra is not affiliated with any other group. The North Sumatra MUI has issued a fatwa prohibiting the Inkar Sunnah. However, the spread of Inkar Sunnah is still found in people's lives